Influence of fluoride in poly(d, l‐lactide)/apatite composites on bone formation. Issue 4 (18th August 2014) - Luo, X.; Barbieri, D.; Passanisi, G.; Yuan, H.; de Bruijn, J. D.
Abstract: The influence of fluoride in poly(d, l ‐lactide)/apatite composites on ectopic bone formation was evaluated in sheep. Nano‐apatite powders with different replacement levels of OH groups by fluoride (F) (0% (F0), 50% (F50), 100% (F100), and excessive (F200)) were co‐extruded with poly (d, l ‐lactide) at a weight ratio of 1:1. Fluoride release from the composites (CF0, CF50, CF100, and CF200) was evaluated in vitro and bone formation was assessed after intramuscular implantation in sheep. After 24 weeks in simulated physiological solution, CF0 and CF50 showed negligible fluoride release, whereas it was considerable from the CF100 and CF200 composites. Histology showed that the incidence of de novo bone formation decreased in implants with increasing fluoride content indicating a negative influence of fluoride on ectopic bone formation. Furthermore, a significant decrease in resorption of the high fluoride‐content composites and a reduction in the number of multinucleated giant cells were seen. These results show that instead of promoting, the presence of fluoride in poly(d, l ‐lactide)/apatite composites seemed to suppresses their resorption and osteoinductive potential in non‐osseous sites. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 841–852, 2015.